Sociedade de leitura Hermann Faulhaber: a biblioteca dos imigrantes de “Panambi” /RS (1927-1963) - Schmitt, Denise Verbes (2017)
The dissertation addresses the trajectory of the Reading Society Hermann Faulhaber, that has its origins in the Library founded in 1903, in the old Colony of Neu-Württemberg, current municipality of Panambi/RS. The research focuses on the creation, constitution and maintenance of the Reading Society, as an institution dedicated to the preservation of culture among immigrants/descendants. Thus, it analyzes the Library, in the initial years of formation in the Colony, by the initiative of its owner Hermann Meyer, under the management of Marie and Hermann Faulhaber, and its transformation in the Reading Society in 1927, as well as its characteristics before the collection was confiscated in 1942, due to the nationalization policies adopted by the Estado Novo. The research also discusses the decision of not to close activities of the Reading Society, after the seizure of the books, strategies for recovery of the collection, as well as the restructuring actions, with emphasis on the National Institute of the Book (INL). Finally, the dissertation addresses the role played by Marie Faulhaber in the formation of readers in the Colony, highlighting her trajectory, her studies in Germany and her work in the community. The dissertation allows us to understand the role of the Reading Society, associated with the Faulhaber family, especially in bond with the German culture, through the reading practices of the former Colony of Neu-Württemberg.